ANALISIS KESENJANGAN KOMPETENSI ANGKATAN KERJA MUDA KOTA CIMAHI TERHADAP KEBUTUHAN INDUSTRI 4.0 - Dyah Bayu Framesthi; Hendriady de Keizer; Priatna Kesumah; Delia Subrayanti; Yusar Firmansyah; Zira Durun Nafisah; Neng Rohaeni (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
The acceleration of technological transformation in the industry 4.0 era demands changes in the competency structure of the workforce, especially the younger generation, who are the backbone of regional productivity. Cimahi City, as a center for the manufacturing industry, modern services, and the creative economy, faces a serious challenge in the form of a mismatch between the skills possessed by the young workforce and the needs of digital-based industries. This study aims to analyze the level of competency gap in Cimahi City's young workforce, map industrial skills need in the context of automation and digitalization, and identify the factors causing this mismatch. The study used a Sequential Explanatory Mixed Methods design, starting with quantitative analysis through employment data, job readiness surveys, and industrial structure, then continued with qualitative in-depth analysis through in-depth interviews with industry players (IDUKA), vocational education institutions, and young job seekers. The results of the study indicate that competency gaps occur in two main categories: (1) hard skills including digital literacy, automatic machine operation, CAD/CAM capabilities, basic programming, and data literacy; and (2) soft skills such as communication, teamwork, problem-solving, and adaptability. The mismatch is exacerbated by an adaptive curriculum, minimal industrial internships, limited competency certification, and poor job market information. This study recommends strengthening the IDUKA link and match, reformulating the vocational curriculum based on industry needs, accelerating certification, and preparing the 2026–2030 Vocational Action Plan as strategies to increase the competitiveness of Cimahi City's youth.